Bioactive Compounds and Health Benefits of Wasabi (Eutrema Japonicum): Antibacterial, Cytotoxic, and Anti-inflammatory Properties of Root and Leaf Extracts - Daniella, Rafaella; Wang, Wenbin; Hellman, Bernhard; Suryoprabowo, Steven (CV. Media Inti Teknologi, 2025)
Background of study: Eutrema japonicum, commonly known as wasabi, is a perennial plant native to Japan and a member of the Brassicaceae family. Traditionally used as a pungent condiment in Japanese cuisine, wasabi has garnered scientific interest for its wide array of bioactive compounds with potential therapeutic properties. While its rhizome (commonly referred to as the